2008
DOI: 10.1038/ncpneph0941
|View full text |Cite
|
Sign up to set email alerts
|

Animal toxins and the kidney

Abstract: Envenomation or poisoning by toxins from animals poses an important health hazard in the tropics. Animal toxins are complex mixtures of proteins, peptides, enzymes and chemicals. These toxins exert their effects through modulation of ion channels and receptors, and via direct enzyme action. Depolarization or hyperpolarization of ion channels--caused by most marine toxins, and some snake and insect venoms--results in neuromuscular symptoms that can be associated with hemodynamic changes. Toxin enzymes, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 94 publications
(95 reference statements)
4
30
1
3
Order By: Relevance
“…Thus, a tentative explanation of nephropathy observed in some of the victims (11,66) is that the kidney damage is likely the result of complications from the venom's hematoxic effects mediated through its procoagulant and possibly fibrinolytic actions. This suggestion is in line with the view that the nephropathy was associated with disseminated intravascular coagulopathy (61).…”
Section: Nephrotoxicity Studysupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, a tentative explanation of nephropathy observed in some of the victims (11,66) is that the kidney damage is likely the result of complications from the venom's hematoxic effects mediated through its procoagulant and possibly fibrinolytic actions. This suggestion is in line with the view that the nephropathy was associated with disseminated intravascular coagulopathy (61).…”
Section: Nephrotoxicity Studysupporting
confidence: 76%
“…The injury mechanisms can be either by direct effect of the toxins or secondary to hemostatic defect, intravascular hemolysis, shock, immune response or rhabdomyolysis. Hematoxic and myotoxic venoms from viperids or crotalids are a rich source of enzymes that include phospholipases, endopeptidases, L-amino acid oxidases and metalloproteases which can directly cause cellular damage and kidney injury (60,61). In the present study, D. russellii venom from Myanmar was administered to the positive control group (DV group) to produce acute kidney injury as the venom was known to be highly nephrotoxic (62)(63)(64)(65).…”
Section: Nephrotoxicity Studymentioning
confidence: 99%
“…Resolving this controversy is somewhat difficult and requires further research in other areas. Second, it was previously reported that kidney impairment or failure due to scorpion envenoming, especially in the case of H. lepturus is one of the early symptoms and the scorpion venom is toxic (6,(15)(16)(17). While in the present study, kidney problems were present only in patients with blood cell lysis and hemoglobinuria.…”
Section: Discussioncontrasting
confidence: 50%
“…In cases of severe envenomation, snake venom can induce the release of auto pharmacological vasoactive substances, particularly bradykinin, resulting in vasodilatation and myocardial depression, and consequently reduce myocardial contractility [32] . Therefore, our findings support the pathophysiology of sAKI as multifactorial, including hemodynamic changes, direct toxicity of snake venom, immunologic reaction and pigmenturia [33] . This pathophysiology would explain pathological observation of tubular necrosis, mesangiolysis, cortical necrosis, vasculitis, glomerulonephritis, interstitial nephritis, and renal infarction after snakebite envenomation [33] .…”
Section: Resultssupporting
confidence: 48%